2014
DOI: 10.1002/jsfa.6678
|View full text |Cite
|
Sign up to set email alerts
|

Product characteristics and quality of bovine blood‐enriched dried vegetable paste

Abstract: The addition of bovine blood to vegetable paste by linear programming increased the protein content of the paste and improved its functional properties and digestibility. The powder obtained from the spouted bed drier showed suitable functional and nutritional properties and was also a good source of antioxidant compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…All the vegetables and the soybean oil were purchased on local market (Rio Grande, RS, Brazil), and the whey powder was donated by the University of Vale do Taquari (Lajeado, RS, Brazil). The constituents were choice based on its phytochemical contents and their availabilities throughout the year, and its centesimal compositions and caloric values were determined in previous work (Rocha et al 2014).…”
Section: Feedstock Formulation and Obtaining Of Whey Enriched Vegetamentioning
confidence: 99%
See 3 more Smart Citations
“…All the vegetables and the soybean oil were purchased on local market (Rio Grande, RS, Brazil), and the whey powder was donated by the University of Vale do Taquari (Lajeado, RS, Brazil). The constituents were choice based on its phytochemical contents and their availabilities throughout the year, and its centesimal compositions and caloric values were determined in previous work (Rocha et al 2014).…”
Section: Feedstock Formulation and Obtaining Of Whey Enriched Vegetamentioning
confidence: 99%
“…The restricted nutrients were carbohydrates, proteins, lipids and caloric value, the minimum and maximum limits established as restrictions were of 0.50-0.70 (g g -1 ), 0.15-0.20 (g g -1 ), 0.04 (g g -1 ), and 2.00-5.00 (kcal g -1 ), respectively. The lipid content was set at a concentration of 0.04 g g -1 according to previous work (Rocha et al 2014), which showed a good circulation of the polyethylene inert particles in the bed, then, it was not necessary to vary this restriction. The software allowed to perform the optimization, being that the objective function was of the protein content maximization.…”
Section: Feedstock Formulation and Obtaining Of Whey Enriched Vegetamentioning
confidence: 99%
See 2 more Smart Citations